Work Engagement and Employee Well-Being as Predictors of Organizational Productivity - Admiral Admiral (Yayasan Aya Sophia Indonesia, 2026)
In contemporary work environments, organizations face declining productivity while grappling with challenges related to employee burnout and disengagement. Human-centered management approaches increasingly highlight the significance of work engagement and employee well-being as strategic resources in enhancing organizational productivity. This paper aims to explore the predictive roles of work engagement and well-being on organizational productivity, employing qualitative methodologies to synthesize and analyze current organizational practices. Through semi-structured interviews with employees, managers, and human resource leaders, the findings underscore the interdependence between engagement dimensions—such as vigor, dedication, and absorption—and well-being facets, including psychological and emotional aspects, in fostering a sustainable productivity framework. This research contributes to the existing literature by emphasizing a holistic view of productivity that encompasses organizational policies informed by human experience, thereby offering practical insights for managers and policymakers in various sectors.